Work-Integrated Learning for lecturers at a TVET college in the Western Cape - Oosthuizen, L. J.; Spencer, J.; Chigona, A. (South African Journal of Higher Education, 2021)
TVET colleges in South Africa are primarily tasked with preparing students for the workplace. However, employers noted dissatisfaction in the skills and abilities of students entering the workplace. A possible reason for the poor preparation of students may have been found in past research. The curriculum at TVET colleges, as elsewhere in higher education, is very Eurocentric and theoretical in nature. The need for decolonisation of the curriculum thus arises. A decolonized curriculum prepares students to work in a variety of social contexts and considers issues like poverty, inequality and unemployment. A decolonized curriculum needs to include content and context derived from local sources, and need to connect theory with practice. It is thus expected of TVET lecturers to interpret and link theoretical content from the curriculum to the needs of local sources, workplaces and industry. TVET lecturers thus need to have knowledge and experiences from a variety of backgrounds. Past research indicated certain lecturers lack workplace experience and qualifications. It was found that intermediate and FET (grade 10‒11) qualified teachers and graduates from universities who lack workplace experience are employed at TVET colleges. Lecturers who lack workplace experience may find it difficult to link content with the needs of the industry for which they have to prepare their students and may not know how to link theory with practice during lessons. Teaching and learning at TVET colleges require concrete experiences and deliberate encounters. Actual, concrete experiences change the perspectives of students and lecturers and affects them profoundly, which can be seen as a pedagogic piligrimage (Davids and Waghid 2019, 7). To address the latter, SSACI, a Swiss-South African initiative launched a work-integrated learning (WIL) project to identify lecturers that are only equipped with a teaching qualification and lack workplace experience. The work-integrated learning program flared up lecturer’s experience of work-integrated learning and increased motivation and enthusiasm, as they were able to integrate the examples learned from the workplace, to make lessons and lesson preparation more interesting. In addition, lecturers were able to tell students what to expect after graduation when they enter the workplace. A factor that negatively influences the effectiveness of work-integrated learning is the lack of policy supporting the program.